On the Admissibility of the Fixed Points Set of a Mapping with Respect to Another Mapping - Bessem Samet (Mathematics, 2021)
Let <semantics>(M,δ)</semantics> be a metric space, <semantics>f:M→M</semantics>, and <semantics>g:M→[0,+∞)</semantics>. In this paper, we obtain sufficient conditions under which the set of fixed points of f is g-admissible, i.e., <semantics>Fix(f)≠∅</semantics> and <semantics>Fix(f)⊂g−1<mfenced close=")" open="("><mfenced close="}" open="{">0</mfenced></mfenced></semantics>. Some special cases of our main results are discussed and some examples are given.